2022
DOI: 10.3389/fnut.2022.857393
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Inorganic or Amino Acid-Chelated Zinc on Mouse Myoblast Growth in vitro and Growth Performance and Carcass Traits in Growing-Finishing Pigs

Abstract: This study aimed to investigate the effects of the supplementation of different sources of zinc on mouse myoblast growth in vitro and the growth performance and carcass traits in growing-finishing pigs. In the in vitro trial, 25 or 75 mM zinc sulfate (ZnSO4), methionine-chelated zinc (ZnMet), and glycine-chelated zinc (ZnGly) were co-cultured with the myoblast during proliferation and differentiation. The results showed that the amino acid-chelated zinc supplementation, especially ZnMet, enhances cell prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…Preparations for zinc supplementation have evolved from inorganic zinc agents to organic zinc agents [ 87 ]. Inorganic zinc agents have the disadvantages of strong intestinal irritation and low bioavailability [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preparations for zinc supplementation have evolved from inorganic zinc agents to organic zinc agents [ 87 ]. Inorganic zinc agents have the disadvantages of strong intestinal irritation and low bioavailability [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results were partly in accordance with the results of Liu et al [ 23 ], who reported that dietary supplementation with 150 mg/kg ZnMet showed a higher concentration of zinc in the liver in piglets. Furthermore, Zhang et al [ 43 ] reported that the supplementation of ZnMet to growing-finishing pigs significantly increased the concentrations of zinc in the muscle, liver, kidney, and serum in comparison with the ZnSO 4 supplementation. In addition, Jahanian et al [ 19 ] found that incremental levels of ZnMet increased zinc concentrations in the liver and thymus of broiler chicks.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary supplementation with OTMs has the potential to improve meat quality characteristics. It has been reported that amino acid-chelated zinc supplementation could enhance cell proliferation and differentiation in myoblasts ( 10 ). Moreover, OTMs could reduce drip loss by 4–6 days postmortem, which is important for prolonging the shelf life of pork ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most of the amino acid-chelated trace minerals used in the previous studies were single amino acid chelates, such as Gly-Fe, Gly-Zn, and Met-Zn (10)(11)(12)(13). In this study, we used a novel compound, an amino acid-chelated trace mineral product, containing 18 types of amino acids.…”
Section: Introductionmentioning
confidence: 99%